Carbon nanofibers/nanosheets hybrid derived from cornstalks as a sustainable anode for Li-ion batteries1. Issue 13 (7th April 2015) - Wang, Shengbin; Xiao, Changlei; Xing, Yalan; Xu, Huaizhe; Zhang, Shichao
<x xml:space="preserve">Abstract</x> A porous carbon nanofibers/nanosheets hybrid (CNFS) is converted from cornstalk waste, and displays a superhigh surface area and rich porosity. Benefiting from unique structural features, the evolved CNFS possesses an ultrahigh rate capability of 454 mA h g−1 at 3 A g−1.